PROTEIN RESIDUE ANALYSIS OF LITHIC ARTIFACTS FROM SITES HaRf-51, HaRf-52, HaRf-70, HaRf-71, HaRf-85, HbRf-65, HbRf-102, AND HbRf-132 IN BRITISH COLUMBIA, CANADA - Milligan, Jennifer L.B. (PaleoResearch Institute) (the Digital Archaeological Record)
Eight subsurface pre-contact sites (HaRf-51, HaRf-52, HaRf-70, HaRf-71, HaRf-85, HbRf-65, HbRf-102, and HbRf-132) of varying size are situated on knolls and ridges near the confluence of the Peace and Moberly Rivers, British Columbia, Canada. Conventional radiocarbon dates for the sites range between 11,220 ± 40 BP and 1770 ± 30 BP (Shauna Huculak, personal communication April 24, 2015). Nine lithic artifacts and associated soil control samples collected from the sites’ assemblages were submitted for protein residue extraction and testing.